PENINGKATAN KEMAMPUAN DAN KREATIVITAS SANTRI PONDOK PESANTREN DAARUL ULUUM BANTAR KEMANG KOTA BOGOR MELALUI PELATIHAN MEMBUAT GANTUNGAN POT BUNGA - La Diadhan Hukama; Zainal Zawir Simon; Effendy Zain; Verni Yuliaty Ismail; Lily Deviastri; Elmanizar Elmanizar; Suhirman Madjid; Lenda Komala; Masagus Asaari (Jurnal Abdi Insani, 2023)
Creativity is the result of a relationship between talents, processes, and the environment in which individuals or groups create new and useful products. Creativity knows no age. From childhood to old age. This activity aims to foster creativity and improve the skills of OSIS Board of Daarul Uluum Bantar Kemang Islamic Boarding School, Bogor City through training in making flower pot hangers. The method used in this activity is Community Development Practice and combined with the Peer Assisted Learning Model. The trainees were able to make several models of flower pot hangers from kur rope, cloth rope and cotton rope. Through this activity there has been an increase in the ability and knowledge of the students and they are increasingly aware of the importance of creativity in being creative. This is reflected in their enthusiasm for being able to make several models of hanging pots in a relatively short time.